Determinan yang Mempengaruhi Pemanfaatan Pelayanan pada Penderita Hipertensi: Studi Literatur - Agustine, Farina Eka; Idris, Haerawati; Misnaniarti, Misnaniarti (Health Information : Jurnal Penelitian, 2023)
Background: Hypertension is a disease that is the number one cause of death in the world every year. Hypertension can cause complications from various diseases, such as heart attacks, strokes or kidney disease. Therefore, hypertension is a disease that must always be controlled routinely in health facilities. So this study aims to analyze the determinants that influence the use of services for hypertension sufferers. Methods: This research uses the Literature Review method. The approach used is Narrative Literature Review. There are 10 research articles obtained from a database, namely Google Scholar, Pubmed and ScienceDirect. The keywords used are Service Utilization and Hypertension. This method consists of collecting journals and drawing several conclusions and then reviewing them in depth. Research Results: From the 10 articles taken, the results showed that there was a relationship between age, gender, type of membership and region on the use of health services in hypertension sufferers. Conclusion: Utilization of services for hypertension sufferers can be influenced by several variables, namely age, gender, type of membership and region.